Agronomical interventions to mitigate nitrous oxide (N2O) emission in agriculture - A comprehensive review - Ajmal, S S; Ramesh, T; Rathika, S; Sakthivel, K; Kokilavani, S; Akanksha, Mahajan (Plant Science Today, 2025)
Global warming is a critical global concern that poses a serious threat to human life. The release of greenhouse gases (GHG), including methane (CH₄), nitrous oxide (N₂O) and carbon dioxide (CO₂), is a primary driver of climate change. Among these, N₂O is highly potent, with a global warming potential approximately 300 times higher than CO₂, making it a major contributor to climate change. Its emissions mainly originate from agricultural practices, particularly through soil-based nitrification and denitrification processes. N₂O emissions can be mitigated by identifying sources, calculating the emission and adopting mitigation strategies. Agronomic practices play a crucial role in lowering N₂O emissions while maintaining crop productivity. This review discusses N₂O emission mechanisms in agricultural soils and explores various agronomic interventions, including optimal nitrogen fertilizer application, precise timing of nitrogen application, split application, biofertilizers, fertigation, neem-coated urea, proper management of crop residues, cover cropping, crop rotation and conservation tillage. Studies indicate that proper nitrogen supply timing and application methods can reduce emissions by 30-40 %, while adjustments in tillage and irrigation, along with soil amendments like biochar and lime, can lower emissions by up to 80 %. The use of slow-release fertilizers and nitrification inhibitors can cut emissions by 50 %, while arbuscular mycorrhizal fungi treatment can lead to a reduction of up to 75 %. Additionally, crop rotation and integrated nutrient management enhance mitigation efforts. These agronomic approaches can substantially decrease N₂O emissions from soils, mitigate global warming and support sustainable agriculture.